The effect of applying the PLISSIT model of sexual counseling on sexual problems among psychological women (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Women's sexual health is an ongoing practical experience of physical, psychological and social well-being related to sex and an important component of emotional and physical happiness. It is an important aspect that must be taken into consideration in order to improve the well-being and health of women. Research objective : Evaluating the effect of applying the PLISSIT model of sexual counseling on sexual problems among psychological women. Research materials and methods: A quasi-experimental study was conducted on a random sample of 60 women one week after giving birth and up to 6 months after the last birth. They were selected by a simple random method in the women’s clinic at the Al-Assad Medical Complex in Hama, the women’s clinic at the Family Planning Center, and the women’s clinic in Comprehensive clinics in Hama. They were randomly divided into two groups: a control group of 30 women who were left to the care routine in the clinic, and an experimental group of 30 women (the PLISSIT model for sexual counseling was applied to them). Data were collected through two tools prepared for this purpose. Conclusions: The effectiveness of applying the PLISSIT model for sexual counseling in reducing the rate of sexual problems among women in the postpartum stage. There is no significant relationship between the two groups of the study in terms of the demographic characteristics of the women in the study sample, which indicates the homogeneity of the sample in the two groups.. Recommendations: The necessity of adopting the PLISSIT model for sexual counseling in the nursing care provided to women during the postpartum period and after it, educating and training midwives and nurses on how to apply the PLISSIT model for sexual counseling, conducting a similar study on a large sample and from several hospitals that allows generalizing the results that have been obtained.